Nesting habits and colonial productivity of Polistes canadensis canadensis(L.) (hymenoptera-vespidae) in a Caatinga area, Bahia state- Brazil - De M. Santos, Gilberto M. [UNESP]; Gobbi, Nivar [UNESP] (My University, 1998)
The paper aims at increasing the knowledge on the ecology of Polistes canadensis canadensis colonies in a Caatinga region. We studied some aspects of P.c. canadensis nesting habitats and colonial productivity. In the environmental conditions studied, this species nests on several types of substrata, particulary on thorny plants and in caves. The colony productivity and the cell reoccupation rate varies from one colony to another. In some colonies, we found cells with one, two and, more rarely, three reoccupations, this is upto four individuals produced in one cell only. The rate of the first reoccupation was 2.88-34.78%, with na average rate of 15.96%. The number of adults produced by the colonies of P.c. canadensis varied from 10 to 576 individuals. Productivity, given by the relationship between the number of born adults and the number of cell existing in the nest, varied from 31.25 to 123.19% and presented an average of 88.50%.